2021
DOI: 10.3390/ijerph182312488
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Prevalence among Czech Dentists

Abstract: This work evaluates the prevalence of coronavirus disease (COVID-19), a viral infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), among members of the Czech Dental Chamber. The assessment was based on an online questionnaire filled out by 2716 participants, representing 24.3% of all chamber members. Overall, 25.4% of the participants admitted they were diagnosed with COVID-19 by 30 June 2021, with no statistical differences between the sexes. While in the age groups under 50 the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Due to data extension and the different focus of individual chapters, their results were analyzed and presented separately. The results of the Prevalence chapter were published in November 2021, the data of the Vaccination chapter are presented in this work, and the Epidemiology chapter will be analyzed in 2022 [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to data extension and the different focus of individual chapters, their results were analyzed and presented separately. The results of the Prevalence chapter were published in November 2021, the data of the Vaccination chapter are presented in this work, and the Epidemiology chapter will be analyzed in 2022 [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the first half of 2021, the Czech Republic was the fourth most affected country by COVID-19 in the world [ 1 , 2 , 3 ]. Public health restrictions caused by the COVID-19 pandemic severely affected the entire country, including the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of protective equipment for dental teams, an adequate infrastructure as well as the correct management of patients, all contributed to an increase in trust and safety within medical teams [ 24 ]. For example, a recent study conducted in the Czech Republic showed that well-chosen anti-epidemic measures adopted by dental professionals can reduce occupational infection risks associated with SARS-CoV-2 [ 26 ]. On the other hand, other studies examining the knowledge, attitudes and practices of the Turkish pediatric dentists, showed a satisfactory level of knowledge regarding COVID-19 prevention, although infection control measures could have been better implemented [ 27 ].…”
Section: The Impact Of Covid-19 On Dental Staffmentioning
confidence: 99%